Analisis sikap konsumen atas kreatifitas iklan, daya tarik iklan dan kualitas pesan iklan pada handphone merek Iphone 5 di kota Pekanbaru - Satria, Sukma; ', Zulkarnain; ', Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to look at consumer attitudes on advertising creativity , attractiveness and quality advertising product advertising messages on brand mobile phone Iphone 5 in the city of Pekanbaru . Population in this research is that people wear and never watch brand mobile ad Iphone 4s in Pekanbaru . While the sample in this study using purposive sampling method with the criteria of Pekanbaru , adolescent or adult with the age of 15-25 years , and never wear watch mobile ad Iphone 4s brand . The data obtained will then be processed by Fishbein analysis model analysis .From the test results obtained by the consumer attitude ( Ao ) of the value of creativity in advertising has a negative gap . It means that consumer expectations are higher than the perceived during the advertising creativity . Further consumer attitudes ( Ao ) of the advertising appeal has a negative value gap . Artiya that consumer expectations are higher than for the perceived attractiveness of the ad . And consumer attitudes ( Ao ) on the quality of the advertising message has a negative value gap . It means that consumer expectations are higher than for the perceived quality of the advertising message .Keywords : Creativity advertising , advertising appeal and quality of advertising messages.